Controlling localization of Escherichia coli populations using a two‐part synthetic motility circuit: An accelerator and brake. Issue 12 (29th August 2017) - McKay, Ryan; Hauk, Pricila; Wu, Hsuan‐Chen; Pottash, Alex Eli; Shang, Wu; Terrell, Jessica; Payne, Gregory F.; Bentley, William E.
Abstract: Probiotics, whether taken as capsules or consumed in foods, have been regarded as safe for human use by regulatory agencies. Being living cells, they serve as "tunable" factories for the synthesis of a vast array of beneficial molecules. The idea of reprogramming probiotics to act as controllable factories, producing potential therapeutic molecules under user‐specified conditions, represents a new and powerful concept in drug synthesis and delivery. Probiotics that serve as drug delivery vehicles pose several challenges, one being targeting (as seen with nanoparticle approaches). Here, we employ synthetic biology to control swimming directionality in a process referred to as "pseudotaxis." Escherichia coli, absent the motility regulator cheZ, swim sporadically, missing the traditional "run" in the run:tumble swimming paradigm. Upon introduction of cheZ in trans and its signal‐generated upregulation, engineered bacteria can be "programmed" to swim toward the source of the chemical cue. Here, engineered cells that encounter sufficient levels of the small signal molecule pyocyanin, produce an engineered CheZ and swim with programmed directionality. By incorporating a degradation tag at the C‐terminus of CheZ, the cells stop running when they exit spaces containing pyocyanin. That is, the engineered CheZ modified with a C‐terminal extension derived from the putative DNA‐binding transcriptional regulator YbaQ (RREERAAKKVA) is consumed by the ClpXP protease machine at a rate sufficient to "brake" the cells when pyocyanin levels are too low. Through this process, we demonstrate that over time, these engineered E. coli accumulate in pyocyanin‐rich locales. We suggest that such approaches may find utility in engineering probiotics so that their beneficial functions can be focused in areas of principal benefit. Abstract : This study designs E. coli to localize at sites of a chosen chemical cue, a phenomenon called pseudotaxis. It is accomplished by controlling the motility of cells to accelerate and brake accordingly. This paradigm can be used to direct cells towards a variety of compounds of choice, with applications including targeted drug delivery.